Disaggregated cost-benefit analysis incorporating ecosystem services and disservices: A case from SAI Sanctuary - Hounshell, Tyler (Consilience, 2016)
Under private management and ownership, privately protected areas provide opportunities for in situ environmental conservation. These areas also provide ecosystem services and disservices for various stakeholders, but their impact on various stakeholders has not been comprehensively studied. To evaluate the economic impact of a privately protected area, a disaggregated cost-benefit analysis was conducted on SAI Sanctuary incorporating its ecosystem services and disservices on private, local, and global stakeholders over a 10-year period from 2010 to 2020. SAI Sanctuary is a privately protected area located in southern Kodagu, a district in the Western Ghats forests of Karnataka, India. To valuate costs and benefits, interviews were conducted with private and local stakeholders. A literature review integrating other valuation techniques was performed as well. Discount rates of 0% and 6% were selected, and sensitivity analysis yielded various tradeoffs bore by each stakeholder group. Results indicate private stakeholders bear the greatest net costs, and local stakeholders gain the greatest net benefits largely due to pollination, a regulating service valued between 546,210 and 774,810 in the year 2020. Global stakeholders remained the least affected by SAI Sanctuary with net benefits ranging from 27,900 to 39,570 in 2020. Still, the results validate stakeholder predictions that SAI Sanctuary not only sequesters carbon dioxide, it provides a range of ecosystem services while harboring biodiversity and producing natural capital. The results also indicate that environmental conservation occasionally yields unintended tradeoffs with disproportionate costs and benefits. In sum, environmental conservation can have a multiplicity of outcomes, but measuring these outcomes and bringing privately protected areas into strategies for global conservation is vital.